Livelihood of Entrepreneurs of Union Digital Centers in Bangladesh: An Empirical Study - Mohammad Nur Ullah; Nusrat Sharmin Khadiza (Department of Government Studies, Universitas Syiah Kuala, 2021)
Union Digital Centers (UDCs) have changed not just how government services are delivered, but also how entrepreneurs (UDDOKTA) live. This study appraises the demographic status of entrepreneurs of Union Digital Centers in Bangladesh. This study is based on a mixed approach to social research. Data were collected from 45 entrepreneurs of 25 UDCs in the southern part of Bangladesh. This study found most of the entrepreneurs get appointed from local inhabitants with proper training though it has a chance of political influence but regular monitoring has occurred. The entrepreneurs are under the age of 30 with a standard educational background. The reasons for joining at UDCs are to generate income and to enter an independent profession. Among male and female entrepreneurs, the dropout rate is higher regarding female than male counterparts because of their pregnancy or after marital issues. The rate of availability of male entrepreneurs in UDCs is higher than the female counterparts. Although the income of the entrepreneurs has become higher than before joining, low-income generation by male Entrepreneurs is surely a concern if it becomes lower than expectation. However, authorities must take care of the entrepreneurs issues so that they can serve the entire community.